16 The office of the assistant secretary for preparedness and response; strengthening preparedness in the us health system. (1st September 2016) - Carr, Brendan
Abstract : Session Description: The Assistant Secretary of Preparedness and Response (ASPR) is the principal adviser to the US Secretary of the Department of Health and Human Services responsible for pro1viding integrated policy coordination and strategic direction with respect to all matters related to public health, medical preparedness, and deployment of the federal response for public health emergencies and incidents. ASPR focuses on preparedness planning and response; building federal emergency medical operational capabilities; countermeasures research, advance development, and procurement; and grants to strengthen the capabilities of hospitals and health care systems in public health emergencies and medical disasters. The office provides federal support, including medical professionals through ASPR's National Disaster Medical System, to augment state and local capabilities during an emergency or disaster. The presenter is the Director of ASPR's Emergency Care Coordination Centre (ECCC), which is charged with leading federal efforts to create an emergency care system that is patient-and community-centred; integrated into the broader healthcare system; high quality; and prepared to respond in times of public health emergencies. A strong emergency care system serves as the foundation for a health system that is prepared and ready to respond. The talk will provide a high level overview of ASPR's programs and emphasise the intersection of preparedness and response planning in the broader healthcare system.